Evidence of pneumoconstriction in asthmatics. (1st February 2018) - Bokov, Plamen; Delclaux, Christophe
ABSTRACT: Introduction : In asthma, bronchial smooth muscle contraction is responsible for the obstructive ventilatory defect that may be relieved by the administration of bronchodilators. It has been observed that deep inspiration causes dilation of the airways in both asthmatic and nonasthmatic subjects. Pneumoconstriction is a rare manifestation of the contractile cells present in the perialveolar space leading to a restrictive defect in asthmatics. Case study : We present the lung function tests of two asthmatic patients (a boy and a woman) depicting a restrictive defect (pneumoconstriction) that disappeared after salbutamol administration while no improvement was noted in the spirometric data. Results : We observed a particular static lung volume distribution that could be explained by a concept of cellular mechanoresponsiveness called "glassy dynamics" applied to smooth muscle cells. Conclusion : We concluded that the presence of contractile interstitial cells in the perialveolar space could be responsible for the observed anomalies reflecting pneumoconstriction. We explained the observed distribution of static lung volumes by the glassy dynamics of cytoskeleton, a concept that had no clinical validation.